Da interação face a face à consolidação de cenas de atenção conjunta entre irmãos: uma análise dos aspectos multimodais na aquisição da linguagem. - Souza, Andrea Maria Borges de (2016)
The face to face interaction and joint attention are types of interaction that occur in the course of language acquisition. Studies of face to face interaction and joint attention have been conducted in the language area, focusing on mother-child interaction. In our research, we will study these interactions with brother-sister who are still in language acquisition. Our study aims to analyze the multimodal aspects in face to face interactions and joint attention scenes between two children (a boy and a girl) in language acquisition. In our analysis procedure, a longitudinal study was carried out from a boy of thirty-five months at forty-six months and his sister from the first month to the twelfth month of life, both in acquisition language. During our study, homemade recordings were analyzed, which were held by the mother during monthly routines between the brothers over a year. Our research is supported in the context of multimodal functioning of language, based on Kendon (1982, 2000), McNeill (1992, 2000), Calvacante (2009, 2010, 2012), Fonte et al (2014). Our research was also based on works about joint attention, based on conceptions of authors like Bruner (1990), Tomasello (2003), Ávila Nóbrega; Cavalcante (2013) and Fonte (2011), Braz and Salomão (2002). During our analysis, we seek to discuss multimodal elements found in moments of interactive scenes like the gesture, the look and the verbal production. The research result showed us that in interactive contexts between brother-sister, multimodal elements (the gestures, the look and the verbal production) presented by the brother contributed to his sister engagement in relation to interactions and language acquisition. Based on this research result, we realize the importance of multimodal plans: the gesture, the look and the verbal production to the acquisition of language from interactive scenes. This research aims to check more about multimodal operation in language acquisition and consolidation of joint attention in children. It is possible to say that the multi-modal plans, composed of gestures and verbal productions are acquired in continuous moments, which over the time become more elaborate during interactions with the other.